Mobile-assisted Language Learning And Motivation: Can The Use Of Mobile Devices Promote Students’ Motivation In Efl Classes? - Saidouni , Khawla; Bahloul , Amel (الإحياء, 2024)
In the recent years, smart mobile devices are taking over all aspects of human life such as education, work and leisure. In fact, the majority of students are using their handheld devices, mainly smart phones and computer tablets, for the sake of communicating, sharing information and interacting. Ergo, mobile technologies become an essential part of students’ routines. This new wave of technology has created an approach of language teaching and learning known as Mobile Assisted Language Learning (MALL). The current study endeavors to investigate the effectiveness of MALL on learners’ motivation to learn English as a Foreign Language (EFL). It adopts a descriptive method of research which is an amalgam of quantitative and qualitative data. Thus, a questionnaire, which is randomly administered to thirty Master 1 students, is bracketed with a structured interview held with four teachers of English at Batna-2 University. The findings of the study provide us with significant results about the impact of mobile technologies on both the EFL teaching/learning process and motivation. First, students generally consider this new wave of technology as having a positive impact on their own language skills. Second, the results also pinpoint that both teachers and students strongly confirm that the integration of mobile devices in EFL setting fosters the students’ motivation, and increases eagerness toward learning. Thus, it is highly significant to implement the handheld devices in the Algerian EFL classes in order to cope with the challenge of technological and pedagogical shifts occurring in the teaching profession.